Vacuum-assisted closure in the treatment of biliary leakage following gunshot injury to the liver - Şimşek, Arife; Kılcı, Mahmut Burak; Karabulut, Ertuğrul; Sansal, Müfit; Ünal, Bülent (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Şimşek A, Kılcı MB, Karabulut E, Sansal M, Ünal B. Vacuum-assisted closure in the treatment of biliary leakage following gunshot injury to the liver. Turk J Gastroenterol 2019; 30(7): 658-9.